The formation of the Victorian literary profession - Salmon, Richard, 1965- (Cambridge University Press, 2013)
A fascinating study into the development of the Victorian literary profession that examines literary and visual representations of authorship.
Keywords: English literature -- 19th century -- History and criticism.; Authors in literature.; Literature and society -- England -- History -- 19th century.; Authors, English -- 19th century.; England -- Intellectual life -- 19th century.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Écrivains dans la littérature.; Littérature et société -- Angleterre -- Histoire -- 19e siècle.; Écrivains anglais -- 19e siècle.; Angleterre -- Vie intellectuelle -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Authors, English; Authors in literature; English literature; Intellectual life; Literature and society; England; 1800-1899; Criticism, interpretation, etc.; History